DEVELOPING A STRATEGY OF RELATIONS AND COOPERATION OF NON-PROFIT ORGANIZATIONS WITH THE LOCAL COMMUNITY - Mihanovic, Zoran; Rosan, Suzana (European Scientific Journal, ESJ, 2014)
Stakeholder engagement can be described as an effort to understand the needs of key stakeholders and include them in activities and decision-making process. Managing stakeholders strategically is seen as the means for achieving the ultimate goals of organizations. If the stakeholder engagement concept is handled properly it can have a positive impact on the performance of the organization and provide important guidelines for the development of sustainable marketing strategies and practices. The aim and purpose of this research is to determine whether the concept of relationship marketing and stakeholder approach can be successfully applied in the non-profit sector. The study investigates the influence of the local community on the development of business strategies of non-profit organisations (NPOs) and the importance of building and maintaining relationships with the local community, using the example of the Town of Sinj and the region, the knights’ tournament Sinjska Alka as a cultural phenomenon and tourist attraction, the Chivalric Society of the Alka Sinj, Tourist Board and local population. The assumption of this study is that when identifying stakeholders and defining adequate strategy of engagement, managerial perception of stakeholders as well as characteristics of the participants, their attitudes and willingness to engage, should be taken into account. Finally, it is concluded that the engagement of stakeholders in the activities and operations of non-profit organizations has a positive impact on their operations and that it is important for the sustainable development of marketing strategies and practices. Also, the stakeholder participation strategy should be developed bearing in mind the characteristics of the organization’s stakeholders.